Sistem Rekomendasi Pemilihan Program MSIB Bagi Mahasiswa Pendidikan Informatika - Elnursa, Dian Budi; Nofriana, Vesy; Syamsuri, Agus; Cahyani, Laili (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2023)
This study discusses a recommendation system using a content-based filtering method with cosine similarity to help informatics education students choose the right Certified Independent Study and Internship Program (MSIB). The data used is data based on student interests, program and course data available on the MSIB web portal. The content-based filtering method is used to consider the suitability between student preferences and the MSIB program curriculum, while the cosine similarity algorithm is used to calculate the similarity score between different contents. The development of this recommendation system can assist informatics education students in choosing the MSIB program that is in accordance with the preferences of the student's interest profile. The results of the system evaluation obtained an average precision level of 89.4%, indicating that the list of recommendations provided by the system is very good and very relevant according to user preferences.